Fabrication of Bariumtrisulphide Thin Films as Precursors for Chalcogenide Perovskites - Freund, Tim; Cicconi, Maria Rita; Wellmann, Peter (physica status solidi (b), 2022)
Chalcogenide perovskites are a promising and novel class of materials in the fields of solar cells and related subjects. However, the synthesis of thin films of these materials still is troublesome. This work attempts to utilize a phase in the Ba-S phase system with low melting point, namely, BaS3, for the thin-film synthesis of BaZrS3. The successful synthesis of BaS3 thin films is presented and confirmed by field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and Raman analysis. The microstructure of the synthesized BaS3 thin films shows defects and cracks and therefore needs further optimization for the use for BaZrS3 thin-film synthesis. However, the successful synthesis of BaS3 thin films is potentially a great step toward a facile BaZrS3 thin-film synthesis.
CRIS-Team WoS Importer:2022-06-17